The Application of Environmentally Friendly Technology-Based System through Three Holistic Marketing Components: A Case Study - Wijaya, William.s; Paramita, Eristia Lidia; Ihalauw, John J.O.I. (Universitas Brawijaya, Indonesia, 2011)
The roles in enhancing environment sustainability of a company producing gloves was studied. The objectives were to know the application of environmentally friendly technology-based system through internal marketing, societal responsible marketing, and integrated marketing concepts. The research questions: (1) how is the implementation of internal marketing regarding the waste handling; (2) how the societal marketing is implemented in all manufacturing processes; (3) how in accordance with integrated marketing, the green chemistry is carried out through clean technology, friendly environment and availability of raw materials. A case study design with data triangulation was employed. The analysis showed that the company hired and provided an excellent health service for 798 workers from the surrounding areas, fulfilled SR8600 standard and used eco-efficiency machines in its operations. Besides, it adopted ISO 14000, proactively performed societal marketing by producing biodegradable hand gloves, carried out eco-efficiency activities, and managed mutually satisfying relationships with key stakeholders. Finally, to create a green environment, the company performed waste treatment management, adopted energy efficiency measures, ensured the availability of raw materials to make products rapidly degraded by microorganisms hence better environment, and followed the stringent formal rules. The study inductively generated concepts and formulated a set of propositions leading to a proposed model.